2020
DOI: 10.1155/2020/7651610
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Index for Prompt Prediction of Severity in Patients with Unstable Angina Pectoris

Abstract: Objectives. Rapid risk stratification by emergency department (ED) physicians to evaluate patients with chest pain for predicting the short-term occurrence of major adverse cardiac event (MACE) is crucial. The aim of this study was to investigate the predictive value of platelet-lymphocyte ratio (PLR) levels and compare with the modified heart score (m-HS) and stress testing to predict the severity of high-risk patients with unstable angina pectoris (UAP) in the ED. Methods. This study is prospective which inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…Additionally, troponin level has been found to be elevated in not only acute myocardial infarction (AMI), but also in other diseases and complications that cause myocardial damage, such as myocarditis and stress-induced cardiomyopathy [ 10 ]. Studies have shown that troponin may also be useful in the diagnosis of AMI associated with ACS, but not UA [ 12 ]. Therefore, the need for new biomarkers for ACS remains unmet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, troponin level has been found to be elevated in not only acute myocardial infarction (AMI), but also in other diseases and complications that cause myocardial damage, such as myocarditis and stress-induced cardiomyopathy [ 10 ]. Studies have shown that troponin may also be useful in the diagnosis of AMI associated with ACS, but not UA [ 12 ]. Therefore, the need for new biomarkers for ACS remains unmet.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, since chest pain, a typical symptom of ACS, is a common symptom in other diseases, it is difficult to diagnose ACS in patients who report the development of chest pain [ 10 ]. Finally, UA cannot be diagnosed using existing biomarkers, which are typically used to diagnose the existence of myocardial necrosis [ 12 ]. Therefore, the identification of novel ACS diagnostic biomarkers with high specificity and sensitivity is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Troponin levels may be elevated not only in coronary artery disease (CAD) such as ACS but also in other diseases that cause myocardial damage [11]; thus, its positive Downloaded from http://portlandpress.com/bioscirep/article-pdf/doi/10.1042/BSR20210344/911318/bsr-2021-0344-t.pdf by guest on 24 May 2021 predictive value may be limited. Furthermore, these biomarkers may not be useful to differentiate AMI from UA [12], which amplifies the need for new diagnostic biomarkers with high sensitivity and specificity for diagnosing ACS.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the advancements and innovations in diagnostic and interventional methods, evaluation of patients who present to the emergency department with chest pain is still challenging [1][2][3]. Patients who present to the emergency department with chest pain are often thought to have acute coronary syndrome which is a frequent serious health concern among emergency patients [4,5]. Of the patients who present to the emergency department with chest pain, about 20% will receive a diagnosis of acute coronary syndrome and require prolonged stay at the hospital.…”
Section: Introductionmentioning
confidence: 99%